Application of ANN Modelling of Fire Door Resistance - Altin, Mustafa; Tasdemir, Sakir (International Journal of Intelligent Systems and Applications in Engineering, 2016)
Fire doors are compulsorily used in every kind of building nowadays. The determination of fire doorsâ resistance in which kind of buildings is also essential. This determination is needed to be watched through the experimental works done. Computer technologies and applications are commonly used in many fields in industry. In this study, by using the data obtained as a result of experiments made in order to determine the resistance of fire doors, artificial neural network (ANN) model was developed. With this model, it is aimed to evaluate the inner temperature of fire room having an important role in resistance of the fire door. In the developed system, temperature values belonging to thermocouples on the door (Top Left, TopÂ  Right, Middle Left, Middle Right, Bottom Left, Bottom Right (oC) and time (minute) were taken as input parameters and in-room temperature (oC) was taken as output parameters. When the results obtained from ANN and experimental data are compared, it is determined that two groups of data were coherent. It is shown that ANN can be safely used in the determination of fire door resistance.Â